Analysis Of Money Burning Practices in Fruit Relailing, Bojonegoro Regency, Perspective Of Sharia Economic Law - Munir Munir; Rizqi Alfian Rizal; Nurul Huda; Ifa Khoiria Ningrum (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The currently developing economy is developing towards a market orientation where competition occurs in various activities within the national economy. Recently, the development of trade in Bojonegoro has developed, including in fruit retail, namely the Fruit Laskar shop which is famous for having several branches in almost all sub-districts in the Bojonegoro district, discount promos and price discounts are given on the grounds that there is an abundance of stock on the market so they can sell below the market and if it is termed using money burning, predatoring pricing or selling at a loss, business actors deliberately sell at a loss to dominate the market and in the long run to get multiple profits. The results of this study contribute a theory regarding demonstrating the concept of money burning business at Fruit Laskar Fruit Retail in Bojonegoro Regency in accordance with Islamic Economic Law. First, because the terms and pillars of Bai Muwada'ah are fulfilled, Second, when a sale and purchase contract occurs between the buyer and seller voluntarily, the third is related to the terms of transparency in the Bai' Muwad'ah contract, it is not an absolute requirement because the seller is not the buyer, and it is proven in the practice does not contain Ikhtikhar and tadris elements and there is no monopoly because in the current era it is difficult for this to happen, the concept of money burning when viewed from the objective of practice is carried out to dominate the market, gain large profits in the future, and this is what is similar or even similar to the capitalist concept , where actually this money burning is only a stepping stone to further become money capital or money accumulative. The money burning carried out by the Fruit Warriors is to increase the number of buyers and expand their market, in the case of burning money in the form of giving discounts, at the beginning the company had to spend money for various purposes from building systems to marketing.